Pengaruh Penerapan Digital Marketing terhadap Tingkat Pendapatan UMKM Tenun Ikat di Kabupaten Sikka - Mariani Sarah Colson Mbadhi Tani; Pipiet Niken Aurelia; Henrikus Herdi (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
This research aims to analyze the effect of implementing digital marketing on the income level of ikat weaving MSMEs in Sikka Regency. The method used in this research is a quantitative method. The population in this research is MSME actors in the Sikka Regency area with a sample size of 70 ikat weaving actors. The sampling technique used a saturated sample technique with a sample size of 70 respondents. In this research, the type of data used is primary data. The data collection procedure uses a questionnaire which is measured using a Likert scale. The data analysis technique used in this research uses a simple linear analysis method with descriptive statistical tests, data quality tests, classical assumption tests, hypothesis tests and R2 coefficient of determination tests. The research results show that: (1) digital marketing (x) has a significant effect on income levels (y).